2018
DOI: 10.1016/j.redox.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A robust and versatile mass spectrometry platform for comprehensive assessment of the thiol redox metabolome

Abstract: Several diseases are associated with perturbations in redox signaling and aberrant hydrogen sulfide metabolism, and numerous analytical methods exist for the measurement of the sulfur-containing species affected. However, uncertainty remains about their concentrations and speciation in cells/biofluids, perhaps in part due to differences in sample processing and detection principles. Using ultrahigh-performance liquid chromatography in combination with electrospray-ionization tandem mass spectrometry we here ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 82 publications
5
69
0
Order By: Relevance
“…This clearly indicates that MBB can shift the speciation of sulfur species in human serum and plasma and extract sulfide from different biological sulfide pools as we proposed previously (see Nagy et al ., ). A previous study found that more sulfide is detected in whole blood when using NEM or MBB compared with when using IAM, which is consistent with our proposal that NEM and MBB can more effectively cleave polysulfur chains than IAM (Sutton et al ., ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This clearly indicates that MBB can shift the speciation of sulfur species in human serum and plasma and extract sulfide from different biological sulfide pools as we proposed previously (see Nagy et al ., ). A previous study found that more sulfide is detected in whole blood when using NEM or MBB compared with when using IAM, which is consistent with our proposal that NEM and MBB can more effectively cleave polysulfur chains than IAM (Sutton et al ., ).…”
Section: Resultsmentioning
confidence: 95%
“…Similar reactions may occur with the corresponding NEM polysulfide adducts. Such a behaviour would also be consistent with another recent observation, that is, that the NEM adduct of S 2 2− is not stable at pH 7.4 (Sutton et al ., ), supporting the notion that NEM‐derivatized and IAM‐derivatized polysulfide adducts are metastable and both, NEM‐S and IAM‐S are good leaving groups. We used DMPO trying to capture sulfur‐centred products generated upon homolytic cleavage of GSH polysulfide species under two different conditions (using alkylated polysulfides and non‐alkylated polysulfides) but were unable to detect DMPO adducts under any experimental condition (see ).…”
Section: Resultsmentioning
confidence: 99%
“…While it has been proposed that addition of NEM in higher concentrations to blood tubes before plasma preparation can potentially lead to leakage of GSH-NEM from the RBCs [10], our final NEM concentration (2.5 mM) was well below the range where leakage was observed. Delays between sample collection and NEM addition resulted in a reduction of measured reduced-to-oxidized-glutathione ratios in serum and plasma but not in whole blood (Figure 4).…”
Section: Impact Of Sample Processing On Gsh/gssg Determination In Bloodmentioning
confidence: 60%
“…While it has been proposed that addition of NEM in higher concentrations to blood tubes before plasma preparation can potentially lead to leakage of GSH-NEM from the RBCs [10], our final NEM concentration (2.5 mM) was well below the range where leakage was observed.…”
Section: Impact Of Sample Processing On Gsh/gssg Determination In Bloodmentioning
confidence: 60%
See 1 more Smart Citation